Ultrathin high-temperature ferromagnetic rare-earth films: GdScGe and GdScSi monolayers - Wang, Rui; Hou, Lipeng; Shi, Puyuan; Cheng, Qianshuai; Zhang, Yungeng (Frontiers in Physics, 2023)
Two-dimensional (2D) ferromagnetism with robust room-temperature ferromagnetism has sparked intense interest for future miniature information storage devices. However, most 2D ferromagnetic materials have a low Curie temperature. Here, by using density functional theory, two rare-earth monolayers, the GdScSi monolayer and the GdScGe monolayer, were predicted, in which these two monolayers exhibit ferromagnetic orders with large magnetic moments of approximately 7 μB/Gd. Monte Carlo simulations predict Curie temperatures of approximately 470 K and 495 K for the 2D GdScSi monolayer and the GdScGe monolayer, respectively. The spin band calculations show that they are metal. In addition, these two monolayers exhibit dynamical, mechanical, and thermal stabilities. The combination of these novel magnetic properties makes these 2D ferromagnetic crystals promising candidates for high-efficiency spintronic applications.